METAPHOR IN ATTICUS' SELECTED POEMS - Tasyaa' Zulfadhlina; Rahmadsyah Rangkuti; Dian Marisha Putri (JOURNAL OF LANGUAGE, 2022)
What distinguishes literary works from other written non-literary works is the aesthetic value gained by using figurative language in most of literary works. There are various types of figurative language with different usages for each type. Metaphor is a type of figurative language used in literary works and becomes the focus of this study. Atticus is one of the famous poets in social media where his works have been published since 2017. This study aims to identify the types of metaphors found in the selected poems of Atticus', based on theory by Lakoff and Johnson (2003). The method used in this study is descriptive qualitative. The data of this study are sentences in which the metaphorical expressions are marked in italics. The data sources are the poems taken from Atticus' book entitled Love Her Wild, with a total of 20 poems selected. The results of this study show that all types of metaphor: structural metaphor, orientational metaphor, and ontological metaphor are found in the selected poems, where ontological metaphor becomes mostly found type.